Ontology and Ethics in Mass Media - Abarca Fernández, Ramón (2012)
This qualitative research analyzes Decree Inter Mirifica (1963), which states the responsibility of Mass Media and its relation to Culture, Science, Multiculturalism, as well as the technologies of the information, Internet, Digital Journalism and historicalecological Communication Perspective, concluding that Inter Mirifica expresses the essence of Media: its use requires righteousness, prudence and wisdom.